A Diarylacetonitrile as a Molecular Probe for the Detection of Polymeric Mechanoradicals in the Bulk State through a Radical Chain‐Transfer Mechanism. (1st December 2020) - Yamamoto, Takumi; Kato, Sota; Aoki, Daisuke; Otsuka, Hideyuki
Abstract: Since the beginning of polymer science, understanding the influence of mechanical stress on polymer chains has been a fundamental and important research topic. The detection of mechanoradicals generated by homolytic cleavage of the polymer chains in solution has been studied in many cases. However, the detection of mechanoradicals in the bulk is still limited owing to their high reactivity. Herein, we propose an innovative strategy to detect mechanoradicals visually and quantitatively using a chain‐transfer agent that generates relatively stable fluorescent radicals as a molecular probe. Mechanoradicals generated by ball milling of polystyrene samples were successfully detected by using a diarylacetonitrile compound as a fluorescent molecular probe through this radical chain‐transfer mechanism. This probe enables the visualization and quantitative evaluation of mechanoradicals generated by polymer‐chain scission. Abstract : A fluorescent molecular probe that functions as a scavenger of polymeric mechanoradicals was developed (see picture), and its fluorescence intensity was found to increase with increasing generation of radicals in the bulk. This probe enables the optical visualization and quantitative evaluation of polymeric radicals generated by polymer‐chain scission of polymers that do not contain mechanophores.